STUDI TENTANG BAKTERI ESCHERICHIA COLI DAN LOGAM BERAT DALAM ES BATU YANG DIGUNAKAN PEDAGANG DI SEPANJANG PANTAI PURUS KOTA PADANG - Yanti, Eli - (STKIP PGRI Sumbar, 2014)
The objectives of this study to know the content of Escherichia Coli bacterium and heavy metals in ice cubes that used by merchants along of Purus Beach, Padang City. The type of this research is descriptive research that leads to disclosure of the facts and analysis needed. The sample selection in this study using purposive sampling method so that be obtained 3 types of ice cubes that used by merchants, which are the ice blocks, the ice crystals and the plastic ice packs. The tests of three samples was conducted in UPTD. Health Laboratory, Gunung Pangilun, Padang. The result of the laboratory test explained that the content of the bacterium Escherichia Coli in that three samples are the ice blocks samples contained 96/100 ml, the ice crystals samples contained 15/100 ml and the plastic ice packs samples contained 15/100 ml. The Heavy Metal content in the ice cubes that used by merchants are still in the maximum levels that permitted based on the Regulation of the Minister of Health No.492/MENKES/PER/IV/2010 regarding drinking water quality requirements, which are the Metal Iron (Fe) that contains in the ice blocks 0.215 / 0.3 mg / l, ice crystals 0,071 / 0.3 mg / l, plastic ice packs 0,088 / 0.3 mg / l. Metal Copper (Cu) that contains in the ice blocks 0.002 / 2 mg / l, ice crystals <0.002 / 2 mg / l, ice pack plastic <0.002 / 2 mg / l. Metal Lead (Pb) contains in the ice blocks <0.003 / 0.01 mg / l, ice crystals <0.003 / 0.01 mg / l, plastic ice packs <0.003 / 0.01 mg / l. Based on the results of laboratory analysis above it can be concluded that the ice cubes that used by merchants along of Purus Beach Padang City are not suitable for consumption directly because it contains Escherichia Coli Bacteria levels that exceed the maximum allowed by regulation of the Minister of Health No.492/MENKES/PER/IV/2010 regarding drinking water quality requirements.